THE INFLUENCE OF WORKLOAD AND MOTIVATION ON EMPLOYEE PERFORMANCE THROUGH JOB SATISFACTION AT PT JASA RAHARJA NORTH SUMATRA BRANCH - Dwi Haryanto; Prihatin Lumbanraja; Vivi Gusrini Rahmadani (CV. Radja Publika, 2025)
The study examines the impact of workload and motivation on employee performance, with job satisfaction acting as a mediating variable, at PT Jasa Raharja North Sumatra Branch. A quantitative approach using path analysis was employed to assess relationships among variables. Data were collected through a structured questionnaire from employees selected via proportionate stratified random sampling. The findings indicate that workload negatively affects job satisfaction, while motivation positively influences both job satisfaction and employee performance. Additionally, job satisfaction significantly enhances performance and serves as a crucial mediator in the relationship between workload, motivation, and performance. These results highlight the importance of managing workload efficiently and fostering motivation to improve employee job satisfaction and overall performance. The study provides valuable managerial implications, suggesting that organizations should optimize workload distribution and implement motivation-enhancing strategies to maximize employee productivity. By integrating job satisfaction as a strategic factor, companies can create a more conducive work environment, ultimately leading to better performance outcomes. This research contributes to the existing body of knowledge by confirming the mediating role of job satisfaction in workplace dynamics and offering practical insights for corporate human resource management.